Factors that determine cell fate in mitotically arrested cancer cells - Ashraf, Naghmana; Kassim, Roaa; Goldstein, Edward; Landfair, Taylor; Nuñez, Clarissa G.; Arterburn, Jeffrey B.; Shuster, Charles B. (Frontiers in Cell and Developmental Biology, 2026)
IntroductionCancer cells display a high degree of heterogeneity in their responses to mitotic arrest, from apoptosis during mitosis to surviving mitotic failure and continuing to progress through the cell cycle. Thus, understanding the basis for this variation may prove valuable for developing more effective chemotherapeutic strategies.MethodsA combination of biochemical and long-term live cell imaging approaches were applied to determine whether inhibition of Phosphoinositide 3-kinase (PI3K) signaling affected apoptosis in cancer cells arrested in prometaphase with a Kinesin Spindle Protein (KSP) inhibitor.ResultsDual inhibition of KSP and PI3K signaling induced apoptosis more effectively than mitotic arrest or PI3K pathway inhibition alone. Live cell imaging with probes for mitotic progression and apoptosis revealed that HeLa cells that died during mitotic slippage underwent apoptosis during prometaphase arrest, suggesting that PI3K inhibition dramatically shifted the dynamics of cell death. Similar potentiation of mitotic cell death could be detected in SiHa cells, whereas other cancer or non-transformed cell lines were not sensitized by PI3K inhibition. Expression of constitutively active Rap1, which modulates both cell adhesion and PI3K activity, significantly increased the duration of mitotic arrest in a PI3K-dependent manner. Moreover, activated Rap1 significantly increased the fraction of cells that slipped completely back into interphase prior to apoptotic cell death.ConclusionsThese results shed insights into possible mechanisms by which cells may evade cell death during mitotic delay and suggest a strategy to optimize antimitotic interventions.